Pattern of Corporate Ownership in India – Effects of Liberalization - Maiti, Sajal Kumar (Indian Journal of Finance, 2009)
In the midst of much controversy our country ultimately adopted the liberalization policy in July24, 1991. Since then, it is more than a decade we have passed and tasted the effects of liberalization, whether good or bad. In the present article, a humble attempt has been made to review the impact of liberalization particularly in the area of corporate ownership pattern. The thrust of this article is the pattern of corporate ownership in our country. Here an attempt has been made to depict a comparative picture of corporate ownership both in the pre-and post-liberalization eras. Section-I covers the picture of corporate ownership in the pre-liberalization period. Section-II covers the picture of corporate ownership in the post-liberalization period. Areas of the study include distribution of shareholding population in different Indian cities, their density, ranking, industry-wise shareholding pattern, and occupation-wise shareholding pattern. 12 tables contain vital and some rare information on this subject. However, Bombay Stock Exchange (BSE) continued to dominate the scenario, accounting for 32% of the Total Market Turnover even in 1998-99. Corporate culture in our country has remained concentrated only in a few cities, accounting for 55% of the total investor population of our country. Among the investors' categories, Households and Financial Institutions dominate the picture. These two categories jointly account for about 60% of total investment in our country. Table-8 contains much essential information about industry-wise investment pattern of different categories of investors. The pattern of corporate ownership in our country after liberalization has been dominated by the Promoters, both Indian and Foreign, accounting for nearly 50% of the total ownership followed by Institutional Investors, dominated by Foreign Institutional Investors (FIIs). General Public Share is only about 18%, a sharp fall from their position in 1995. Occupation-wise classification of ownership shows that businesspersons dominated the list followed by service holders and housewife categories. On the whole, the object of broad base of corporate ownership has not been achieved.